MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS MULTIKULTURAL SEBAGAI UPAYA PENANAMAN KARAKTER PADA SISWA SEKOLAH DASAR SANGGAR ANAK ALAM (SALAM) NITIPRAYAN KASIHAN BANTUL YOGYAKARTA - Rohinah Rohinah (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2014)
Diversity is a necessity, and Indonesia is a country that is recognized to have areal diversity, both of the diversity of ethnicity, language, religion, and so on. However, the problem is often the heterogeneity was actually seen as a form of binary opposition of opposing and contradictory. This is what ultimately creates problems and the root of the ongoing conflict. Various cases of violence, conflict in the name of religion, ethnic differences are often a trigger hostility to each other. Added to which it is triggered by an understanding of religious teachings stiff and rigid, especially religious doctrines are submitted by teachers through the process of education in schools. Therefore, there needs to be revitalization of religious learning which is deemed able to accommodate the needs of the people of Indonesia, especially the very plural, is through religion-based multicultural learning. Because the embodiment of religious learning rooted in the process of humanization. As was done by SALAM Elementary School in Nitiprayan Kasihan Bantul.